Challenges Faced by Form Three Students at a Coeducational Denominational Secondary School, Regarding Their Access to Accurate Information About Topics as Outlined in the Sexuality and Sexual Health Component of the Health and Family Life Education Curriculum - Gajadhar, Alana Nalini (My University, 2015)
This study investigated the challenges faced by three Form 3 students as they sought to access accurate information on topics outlined in the Sexuality and Sexual Health (SSH) component of the Health and Family Life Education curriculum at a coeducational denominational secondary school in Trinidad and Tobago. Data were collected through interviews. The findings revealed that, among other challenges, the students’ access to information was hampered by inadequate parental communication and insufficient information provided at school. Other barriers to access were: 1) their personal embarrassment, 2) their fear of being judged by others, 3) inaccurate sources of information, 4) superficial discussion of SSH topics, and 5) the lack of trust that their enquiries would be held in confidence.
Keywords: Secondary school students; Access to information; Health and family life education; Sex education; Secondary school curriculum; Case; Trinidad and Tobago